Pruritus. Pathomechanism, management and novel treatment - Józefiak, Maciej; Kania, Joanna; Sobkiewicz, Piotr; Kania, Krzysztof; Niekurzak, Karolina; Jędrak, Maciej (Journal of Education, Health and Sport, 2023)
Introduction Itching is an unpleasant sensation that is commonly experienced in the general population. It accompanies many diseases. This sensory experience is burdensome and significantly reduces the quality of life. The mechanism of itching is complex. It involves receptors, the histaminergic and non-histaminergic pathways, cytokines, neuropeptides, neurotransmitters, proteases, and enzymes. External factors such as temperature or capsaicin also influence itching. Aim of the study This review presents the current state of knowledge regarding therapy in the treatment of itching. Also aims to show that it is a complicated process. Pruritus is a very bothersome sensory sensation and is a common symptom. Material and methods This review was based on scientific books on human physiology and dermatology were used, which are listed in the bibliography and available data collected in the PubMed and Google Scholar database. Using key words: itch, management, pathogenesis, pathophysiology, pruritus, therapeutics, treatments. Conclusion The latest research on itching has led to a better understanding of this complex mechanism. As a result, there is a possibility of discovering new, innovative treatment methods that are targeted at specific elements of this process or work systemically. Understanding the broad etiology assists in identifying the cause and in implementing an appropriate therapeutic strategy. Further research will enable improvements in treatment and enhance patient comfort.